Low Cost Autopilot Design Using Fuzzy Supervisory Control - Hadi, Mahmoud (2005)
A Master of Science Thesis in Mechatronics Submitted to the School of Engineering by Mahmoud Hadi, "Low Cost Autopilot Design Using Fuzzy Supervisory Control," May 2005. Chair of Committee Dr. Mohamed Ameen Al Jarrah & Co-Advisor Dr. Abdel Rahman Al-Ali. Available are Soft and Hard Copies of the Thesis.